DENTAL CARRIES CLASSIFICATION USING YOLO V8 - Engr. Syed Muhammad Zia Uddin; Dr. Muhammad Imran Aslam; Dr. Muhammad Moinuddin (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study focuses on the development of a sophisticated caries detection system using deep learning techniques applied to periapical dental X-ray images. By customizing the YOLOv8 architecture, the system was optimized for accurate caries identification. The training process involved intricate customization, including backbone and feature extraction neck integration, and head design. Pre-processing was applied to enhance detection efficiency. Leveraging YOLOv8 elements like the SPPF layer, up-sample layers, and detection modules enabled precise identification of dental caries lesions within X-ray images. The training dataset was meticulously curated with pixel-level annotations by certified dentists to ensure detailed representation. Augmentation techniques like random flipping and rotation were employed to enhance dataset diversity, model generalizability, and standardization. The system’s efficacy is validated using a comprehensive suite of metrics: Mean Average Precision (mAP) of 91.8%, F1-score of 92.0%, and recall of 92.6%. This showcases its proficiency in accurately identifying and localizing caries lesions and other relevant dental conditions within X-ray images. The unique aspect of training the network for detecting five classes (cavity, crown, restoration, missing tooth, and root canal treated) on a preliminary basis using a dataset collected from Pakistani patients in Karachi adds a significant dimension to this study. This approach aligns with recent advancements in deep learning algorithms for dental applications, emphasizing the importance of leveraging modern architectures to improve dental diagnostics and aid in accurate diagnoses based on periapical radiographs.